Using zone theory to understand teacher identity as an embedder-of-numeracy: an analytical framework. Issue 2 (15th March 2022) - Bennison, Anne
ABSTRACT: Teacher identity provides useful insights into the learning and practices of teachers. The complexity of identity, however, makes it difficult to use in empirical research. An analytical framework with two components is presented. This analytical framework comprises a framework for identity as an embedder-of-numeracy, which clearly defines a teacher's identity when promoting numeracy learning across the curriculum, and Valsiner's zone theory, which provides insights into identity formation and trajectories. The analytical framework was developed in the context of an across the curriculum approach to numeracy in the Australian Curriculum where all teachers are expected to explicitly attend to numeracy in the subjects they teach. A theoretical approach was used to propose the analytical framework which was subsequently tested and refined through an empirical study. Using the analytical framework to guide data collection and analysis in the empirical study suggests the approach has potential to inform professional learning to assist teachers to promote numeracy learning through the subjects they teach. More broadly, the approach taken addresses some of the criticisms and challenges of using identity as a theoretical lens in empirical research by enabling researchers to provide an adequate definition and operationalise identity for a particular context.